Historical Materialism and the Writing of Canadian History: A Dialectical View - Palmer, Bryan (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2006)
AbstractSurveying the historical writing in Canada that has adopted the approach of historical materialism, this paper presents a new perspective on Marxist theory and its relevance to the study of the past. It both links Canadian historical materialist texts to a series of important international debates and suggests the significance of dialectics in the development of Marxism's approach to the past.